The impact of entrepreneur education on business performance / Ahmad Suffian Mohd Zahari ... [et al.] - Mohd Zahari, Ahmad Suffian; Mahmood, Rosman; Yaacob, Najihah Marha; Ibrahim, Norlaila; Nik Jaafar, Nik Fazlin Hiryati (2020)
Entrepreneurship has become an issue in this new era. It has gained a lot of attention by many countries as it acts as the prime mover of economic growth. The importance of entrepreneurial role in supporting the country's economic growth has also been recognized by experts in the field of entrepreneurship. At present, the importance of entrepreneurship has become increasingly important where it has become a priority for developed countries including Malaysia. Thus, the Malaysian Government has recognized the contribution of entrepreneurship to the Malaysian economy. This can be seen when the emphasis on entrepreneurship education in Malaysia has been implemented since 2003 at public universities. In this regard, students at public universities are encouraged to become entrepreneurship as a career since the job market becomes more competitive today. Now, there are many higher educational institutions that are aware of the importance of applying entrepreneurial skills in higher education. Therefore, public universities have to implement entrepreneurship education to encourage students to venture into entrepreneur ship. Recognizing the importance of entrepreneurial contribution to the country, various steps to foster entrepreneurship are being implemented. The Institute for Higher Education (HEI’s) entrepreneurship development policy has also put in a lot of effort and encouragement in entrepreneurship development at the local HEIs to produce quality and entrepreneurial graduates who will act as catalysts for the transformation of the national economy. This study examined the effects of entrepreneurship education in influencing business performance in among ITM/UiTM alumni in Malaysia. A total of 250 graduated from various businesses in Malaysia are involved in this study by voluntarily completing the survey questionnaires. A series of statistical analyses were applied including descriptive analysis, reliability analysis, correlation analysis and multiple regressions analysis using the SPSS software. The finding of this study contributed to advance understanding of entrepreneurship education and business performance in a number of important ways. First, the results of the study indicate university curriculum was found to have significant influences on business performance. Second, the results reveal that university role has no significant influence on business performance. With regard to the relationship between relational factors, the results show that relational factor was found to be significantly associated with business performance. Furthermore, the results also indicate that society factor also has significant influence on business performance. Finally, regarding the effect of entrepreneurship values and business, the study revealed that of